HAKIKAT DAN PRINSIP-PRINSIP PEMBELAJARAN AKIDAH AKHLAK - Bukhari (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
In essence, the learning of morals in learning implies a conscious effort made to change behavior, improve self-quality and know something that is not yet known and needs to be known. While aqidah is defined as a belief in God that is embedded in the heart. While morality has the meaning of an attitude, behavior or deed that is embedded or becomes a habit, which is often done without having to think long. In the learning carried out here, it is focused on learning the moral aqidah, from which we can conclude that the moral aqidah learning is: a conscious effort made to form and strengthen belief in Allah in improving self-quality in good and commendable behavior.